Mapping Surface Charge of Individual Microdomains with Scanning Ion Conductance Microscopy. Issue 20 (26th July 2018) - Zhu, Cheng; Zhou, Lushan; Choi, Myunghoon; Baker, Lane A.
Abstract: We further describe a protocol for the investigation of surface charge with scanning ion conductance microscopy. The protocol measures current‐voltage curves at positions close to and far from the surface of interest and reports the differential response. The data can be interpreted in terms of rectification ratios, an intuitive quantity for such studies. With this protocol, we further investigate the effect of electrolyte concentration and study the influence of scan potential on surface charge measurement on chemically modified surfaces. Abstract : Interfacial surface charge : Surface charge is an incredibly important aspect of interfacial reactivity and recognition and is an intrinsic feature of most electrochemical systems. Instrumentation and experiment are described to transduce surface charge with scanning ion conductance microscopy (SICM). Model substrates with islands of charge are prepared and characterized with this approach. The dependence of current response in approach curves as a function of electrolyte concentration over positive and negative surfaces is recorded.